(untitled) (Scientia Agropecuaria, 2024)
Wetlands worldwide face increasing challenges due to human activities such as water extraction, deforestation, and overfishing. These ecosystems are crucial for biodiversity, water retention, and purification. In Ecuador, the “Abras de Mantequilla” wetland exemplifies these pressures. It serves as a vital site for studying the interactions between soil fertility and arbuscular mycorrhizal fungi (AMF) in forest ecosystems. The study focused on the soil fertility, particularly in relation to AMF in "Noah Morán" secondary forest within the Abras de Mantequilla wetland. The key role of AMF in improving soil fertility was highlighted. Soil samples were collected from the root zone of four forest tree species i.e., Guazuma ulmifolia, Albizia guachapele, Eugenia pustulescens, Cecropia peltate. The four investigated soil samples had marginal differences in the soil physicochemical properties. Number of AMF species were found in the four soils in the range of 16 to 39; Number of por Several AMF lowest por the lowest (16) and highest (39) AMF species were found in E. pustulescens and A. guachapele soils, respectively. AMF species ‘Akent’ was the most dominant (abundance #16) AMF species found in the soils of C. peltate. The ranges of Shannon_H and Simpson_1-D values were found to be 1.78-1.9 and 0.79-0.85, respectively. These insights are important to understanding soil-plant-microorganism interactions in promoting sustainable agricultural practices in the Abras de Mantequilla wetland.